Розвиток креативного мислення та його вплив на навчання - Бугай, Д. Ю. (ХНУРЕ, 2021)
In the article, creativity is understood as a rapid flow of change, opportunities that can radically change the vision of long-established things. It should be noted that universities provide space for the development of ideas and decisions on their own initiative, provide more opportunities to realize their potential, the development of creative abilities and skills. A creative approach to learning and working in today's world is the key to success
Keywords: філософія; розвиток креативного мислення